Codesigning a Mental Health Discharge and Transitions of Care Intervention: A Modified Nominal Group Technique - Tyler, Natasha; Wright, Nicola; Grundy, Andrew; Gregoriou, Kyriakos; Campbell, Stephen; Waring, Justin (Frontiers in Psychiatry, 2020)
Background Discharge from acute mental health services has long been associated with mortality, risk, and related adverse outcomes for patients. Many of the interventions that currently aim to reduce adverse outcomes focus on a single group of healthcare professionals within a single healthcare setting. A recent systematic review highlights very few robust interventions that specifically aim to improve communication across services. However the importance of promoting interagency working and improving information flow between services is continually highlighted as a key priority. Methods Using a novel codesign and experience based approach we worked with a multistakeholder group to develop possible solutions to reduce the adverse outcomes commonly associated with discharge from acute mental health services. This utilized a modified Nominal Group Technique and creative problem solving method to follow a four-stage process: Problem Identification, Solution Generation, Decision-Making, Prioritization and Implementation. Thirty-two healthcare professionals and an expert by lived experienced engaged with the process that took place over two stakeholder events. Results Stakeholders at the first event identified and agreed upon 24 potential ideas to improve discharge from acute mental health services. These were refined at the second event to four elements of an interagency intervention: a multiagency ‘Discharge Team’ (with designated discharge coordinator), inclusive technology enabled team meetings, universal documentation and a patient generated discharge plan. Conclusion This is the first study to codesign an interagency mental health discharge intervention based around a discharge team. We developed a model for working that places a greater focus on a patient generated discharge plan, interagency working, and information flow. A pilot of the proposed intervention is now needed to test the feasibility and effectiveness in reducing adverse outcomes.